The determinants and effects of board committees - Lee, Wei-Ming (Journal of Corporate Finance, 2020)
The governance reforms of 2003 require corporate boards to establish various committees. This paper studies how these committees are structured and the corresponding impacts. I find that independent directors with long tenures and multiple board seats tend to multitask and sit on more committees. The firms that multitask their independent directors are associated with comparatively low CEO compensation and high ROA. In particular, the benefits of multitasking independent directors are more pronounced in firms with long-tenured CEOs. I contribute to the literature by showing that board performance depends not only on the directors' identities, but also on their task assignments.